The economic and environment benefits from international co-ordination on carbon pricing: a review of economic modelling studies *This paper is based on the OECD Environment Working Paper No. 173 (https://doi.org/10.1787/d4d3e59e-en). The views expressed here are those of the authors and do not represent the official views of the OECD or of its member countries. The authors are grateful for the comments and suggestions from three anonymous referees as well as from participants of the 5th Strategic Dialogue and the working group meetings of the Carbon Market Platform. We would also like to thank Christoph Klaiber for excellent research support. Funding for this paper is received from the German Federal Ministry of Education and Research (BMBF) within the framework of the Strategy Research for Sustainability (FONA) www.fona.de/en. BMBF funding code: CarPri (01LA1816A). The publication of this article was funded by the Open Access Fund of the Leibniz Association. (20th October 2021) - Thube, Sneha; Peterson, Sonja; Nachtigall, Daniel; Ellis, Jane
Abstract: This paper reviews quantitative estimates of the economic and environmental benefits from different forms of international co-ordination on carbon pricing based on economic modelling studies. Forms of international co-ordination include: harmonising carbon prices (e.g. through linking carbon markets), extending the coverage of pricing schemes, phasing out fossil fuel subsidies, developing international sectoral agreements, and establishing co-ordination mechanisms to mitigate carbon leakage. All forms of international co-operation on carbon pricing could deliver benefits, both economic (e.g. lower mitigation costs) and environmental (e.g. reducing greenhouse gas (GHG) emissions and carbon leakage). There is scope to considerably increase the coverage of carbon pricing, since until 2021 only around 40% of energy-related CO2 emissions in 44 OECD and G20 countries face a carbon price. There is also significant scope to improve international co-ordination on carbon pricing: moving from unilateral carbon prices to a globally harmonized carbon price to reach the 1st round of NDC targets for 2030 can reduce global mitigation cost on average by two thirds or 229 billion. Benefits tend to be higher with broader participation of countries, broader coverage of emissions and sectors and, more ambitious policy goals. Extending carbon pricing to non-CO2 GHG could reduce global mitigation costs by up to 48%. Absolute cost savings from harmonized carbon prices increase by almost 70% in 2030 for reductions in line with the 2 °C target. Most, but not all, countries gain economic benefits from international co-operation, and these benefits vary significantly across countries and regions. Complementary measures outside co-operation on carbon pricing (e.g. technology transfers) could potentially ensure that co-operation provides economic benefits for all countries.